A Review: Propolis As An Antiinflammatory Adjunct Therapy in Chronic Kidney Disease - Depari, Elpiani; Malisie, Ririe Fachrina (Jurnal FARMASIMED (JFM), 2025)
Chronic Kidney Disease (CKD) is a disease with abnormalities of the structure and function of kidney that last for at least 3 months and has an impact on health. Inflammation is a progression factor and outcome of CKD. Diabetes, hypertension, cardiovascular disease, exposure to environmental pollution and use of nephrotoxic drugs develop into CKD through inflammation. Inflammation in CKD caused complications in cardiovascular disease, bone mineral disorders, anemia and immune disorders, as well as reducing the patient's quality of life. Cardiovascular complications are the main cause of CKD patients’ death. Renal replacement therapy such as hemodialysis is not effective enough to overcome the inflammation, because unable to remove intermediate molecules and protein-bound molecules, the majority of which are inflammatory markers such as cytokines, namely TNF-?, IL-1, IL-6 and others. Propolis, a natural bee resin product, has anti-inflammatory effects, because it contains many bioactive phytochemicals such as flavonoids, phenolic acids, esters, diterpenes, aromatic aldehydes, amino acids, fatty acids, vitamins and minerals. It inhibits the production and release of cytokines through inhibiting NF-kB (nuclear factor kappa Beta) activity, reducing COX-2 expression and inhibiting nitric oxide (NO). Many clinical trials of propolis in CKD have been carried out and reported safe and beneficial, including in patients undergoing dialysis. Propolis has been proven able to reduce several inflammatory markers, such as TNF-?, interleukin and others. It has great potential as a safe additional therapy in CKD patients, both dialysis and non-dialysis.